2014
DOI: 10.1186/bf03352234
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the geomagnetic storm associated Dst index using an artificial neural network algorithm

Abstract: In order to enhance the reproduction of the recovery phase D st index of a geomagnetic storm which has been shown by previous studies to be poorly reproduced when compared with the initial and main phases, an artificial neural network with one hidden layer and error back-propagation learning has been developed. Three hourly D st values before the minimum D st in the main phase in addition to solar wind data of IMF southward-component B s , the total strength B t and the square root of the dynamic pressure, √ n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 22 publications
0
41
0
1
Order By: Relevance
“…Wu and Lundstedt (1997) made an Elman recurrent neural network model for the D st variations from IMF B z and the solar wind number density and speed. Although discrepancy between the model and observation sometimes occurs in the recovery phase, and for the accurate reproduction of this recovery phase some arrangement may be needed (Kugblenu et al, 1999), the model of Wu and Lundstedt (1997) showed a remarkably good performance; i.e., the correlation coefficient between the observed D st and the modeled D st is 0.91. Higher correlation coefficient has been reached by the neural network model by Kugblenu et al (1999) The AL index representing substorm activities has been also used as a prediction target, and reasonably good reproduction has been reported, for example, by McPherron (1997), and Gleisner and Lundstedt (1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu and Lundstedt (1997) made an Elman recurrent neural network model for the D st variations from IMF B z and the solar wind number density and speed. Although discrepancy between the model and observation sometimes occurs in the recovery phase, and for the accurate reproduction of this recovery phase some arrangement may be needed (Kugblenu et al, 1999), the model of Wu and Lundstedt (1997) showed a remarkably good performance; i.e., the correlation coefficient between the observed D st and the modeled D st is 0.91. Higher correlation coefficient has been reached by the neural network model by Kugblenu et al (1999) The AL index representing substorm activities has been also used as a prediction target, and reasonably good reproduction has been reported, for example, by McPherron (1997), and Gleisner and Lundstedt (1997).…”
Section: Introductionmentioning
confidence: 99%
“…Such accurate models have been enabled by recent advances in linear/non-linear prediction filter (e.g., McPherron, 1997;Klimas et al, 1998) and in artificial neural network (Wu and Lundstedt, 1997;Kugblenu et al, 1999). In the linear prediction analysis McPherron (1997) showed that 85% of the D st variance is accounted for by the solar wind dynamic pressure and a coupling function expressed by the solar wind speed, IMF B z , and B y .…”
Section: Introductionmentioning
confidence: 99%
“…Many neural and neurofuzzy methods like Multi Layer Perceptron (MLP) neural network (Kugblenu et al, 1999) with back propagation learning algorithm (BP), Radial Basis Function (RBF) neural networks with orthogonal least square (OLS) for center learning of RBFs and recently Adaptive Network-Based Fuzzy Inference System (AN-FIS) are widely used for nonlinear system identification and also for prediction of chaotic time series. In this section we utilize locally linear neurofuzzy models with Lofunction of LLM that is split is change but the validity functions that are the normalized version of membership functions (Eqs.…”
Section: One-step Ahead Prediction Of Dst Indexmentioning
confidence: 99%
“…For the input parameters, these authors used the solar wind density N and velocity V, the magnitude of the interplanetary magnetic field (IMF), and the By and Bz components of IMF. Kugblenu et al (1999) used a multi-layer feed-forward error back-propagation algorithm in their study and obtained good results considering that the training time series consisted of only 20 storms.…”
Section: Introductionmentioning
confidence: 99%